Assessing the effective marketing and employers' perception of the quality of the Diploma in Public Administration of UiTM Sarawak Branch / Kuldip Singh, Prabha Ramakrishnan and Elizabeth Caroline Augustine - Singh, Kuldip; Ramakrishnan, Prabha; Elizabeth, Caroline Augustine (Institute of Research, Development and Commercialization (IRDC), 2007)
This study examines the socio-economic status and employers' perception of work quality of Diploma Public Administration (DPA) graduates' of UiTM Sarawak Branch who graduated over the yearsfrom /997 to 2000. In addition, the study also examines the graduates 'perception ofDPA programs relevance to employability. Our sample consisted of 436 graduates. The response rate for graduates was 36 percent and the employers' response is /7 percent. The study shows that the profile of a typical DPA graduate is below 30 years old, earning less than RM1,500 per month, has Cumulative Grade Point Average (CGPA) of 2.80 and is employed in the Government sector. Our findings indicate that 70 percent of DPA graduates are employed and /4 percent are pursuing higher education. Regarding the DPA curriculum structure, majority of respondents are of the opinion that it is relevant to the job market however more emphasis needto be given to improving the standard of English language amongst DPA graduates. Addition comments request extended industrial attachment, teaching communication skills and Information Communication Technology (ICT) skills. Employers are of the opinion that UiTM DPA graduates exhibit comparable work quality to other local university graduates. DPA graduates also scored well in the generic skills required by employers.